THE ROLE OF ORGANIC CHEMISTRY IN THE DEVELOPMENT OF BIODEGRADABLE POLYMERS - Bilal Aslam; Ahmed Shah; Rustambek Sharipov (Yayasan Adra Karima Hubbi, 2025)
The increasing environmental concerns associated with plastic waste have prompted significant interest in biodegradable polymers. Organic chemistry plays a crucial role in developing these materials, facilitating the design of polymers that can efficiently degrade in natural environments. This study aims to explore the contributions of organic chemistry to the synthesis and characterization of biodegradable polymers. The focus is on understanding how chemical principles can be applied to create materials with improved degradation rates and functional properties. A comprehensive literature review was conducted, analyzing various biodegradable polymers synthesized through organic chemistry techniques. Experimental work involved synthesizing selected polymers, including polylactic acid (PLA) and polyhydroxyalkanoates (PHA), and evaluating their physical and chemical properties through characterization methods such as spectroscopy and thermal analysis. Findings indicate that organic chemistry enables the tailored design of biodegradable polymers with enhanced properties. The synthesized PLA and PHA exhibited favorable degradation profiles and mechanical strengths, demonstrating their applicability in various fields, including packaging and biomedical applications. This research highlights the essential role of organic chemistry in advancing the development of biodegradable polymers.